Short-Sighted Stochastic Shortest Path Problems - Trevizan, Felipe; Veloso, Manuela (Proceedings of the International Conference on Automated Planning and Scheduling, 2012)
Two extreme approaches can be applied to solve a probabilistic planning problem, namely closed loop algorithms and open loop (a.k.a. replanning) algorithms. While closed loop algorithms invest significant computational effort to generate a closed form solution, open loop algorithms compute open form solutions and interact with the environment in order to refine the computed solution. In this paper, we introduce short-sighted Stochastic Shortest Path (SSP), a new model in which solutions computed based on it can be executed for at least t steps as a closed form solution. Using short-sighted SSPs, we present a novel probabilistic planner called Short-sighted Open Loop Planner (SOLP) that bridges the gap between open and closed loop planners by varying the parameter t: as t increases, more actions can be executed without replanning and, for t sufficiently large, a closed form solution is obtained. We prove that SOLP is asymptotically optimal. To the best of our knowledge, SOLP is the unique probabilistic planner that at the same time provides both replanning and optimality guarantees. We empirically compare SOLP with the winners of the previous probabilistic planning competitions and SOLP outperforms all of them in 33.3% of the problems and ties with the best planner in 48.3% of the problems.